A Gamified Approach for Hand Rehabilitation Device - Carneiro, Fernando; Tavares, Rafael; Rodrigues, José; Abreu, Paulo; Restivo, Maria Teresa (International Journal of Online and Biomedical Engineering (iJOE), 2018)
This work details developments made in a system for hand rehabilitation, that aims to improve recovery of fine motor control, mostly for those recovering from stroke. The system consists of an instrumented device that is used to interact with a variety of games designed to improve fine motor control, enhancing rehabilitation practices. These games were tested with actual disabled individuals and therapists, having received overall positive feedback.